Water quality monitoring of the Pirapó River watershed, Paraná, Brazil - Bortoletto,E. C. (2015)
This study aimed to evaluate the water quality of the Pirapó River watershed in Paraná, Brazil, and identify the critical pollution sites throughout the drainage basin. The water quality was monitored during the period from January 2011 to December 2012. Nine points distributed throughout the main channel of the Pirapó River were sampled for a total of 17 samplings. The water quality was evaluated based on the determination of 14 physical, chemical and microbiological parameters. Analysis of the variables monitored in the Pirapó River watershed using factor analysis/principal components analysis (FA/PCA) indicated the formation of three distinct groups of parameters: water temperature (Twater), dissolved oxygen (DO) and a group composed of total suspended solids (TSS), turbidity and nitrite (NO2–). The parameters Twater and DO exhibited a relationship with the seasonality, and the TSS, turbidity, and NO2– levels were correlated with surface runoff caused by rainfall events. Principal component analysis (PCA) of the sampling points enabled the selection of the 10 most important variables from among the 14 evaluated parameters. The results showed that the nitrate (NO3–), NO2–, TSS, turbidity and total phosphorous (TP) levels were related to the soil type, and the parameters DO, electrical conductivity (EC), ammoniacal nitrogen (N-NH3) and thermotolerant coliforms (TC) were related to organic matter pollution, with the P5 sampling site being the most critical site. The ordination diagram of the sampling points as a function of the PCA indicated a reduction from 9 to 5 sampling points, indicating the potential for decreasing the costs associated with monitoring.